Seismic Assessment of Arch Dams Using Fragility Curves - Vandad Kadkhodayan; S. Meisam Aghajanzadeh; Hasan Mirzabozorg (Civil Engineering Journal, 2015)
In the present paper, the IDA approach is applied to analyzing a thin high arch dam. The parameters of Sa, PGA and PGV are used as intensity measure (IM) and the overstressed area (OSA) is utilized as engineering demand parameter (EDP) and then, three limit states are assigned to the considered structure using the IDA curves. Subsequently, fragility curves are calculated and it is showed that the PGA is a better parameter to be taken as IM. In addition, it is found that the utilizing the proposed methodology, quantifying the qualitative limit states is probable. At last, having the fragility curves and considering their slope in addition to the other routine data which can be extracted from these curves, one may be able to conclude that in what performance level the considered dam body seems to be weak and needs retrofitting works.